Genocide and resistance Nr. 8(2) - Maslauskienė , Nijolė; Bubnys, Arūnas; Jonušauskas, Laurynas; Butkus, Zenonas; Kasparavičius, Algimantas; Ilmjärv, Magnus; Tauber, Joachim; Kašauskienė, Vanda; A. Loeber, Dietrich; Žiūkas, Mindaugas; Kuodytė, Dalia; Anušauskas, Arvydas (Genocidas ir rezistencija, 2000)
Full Issue (paper copy scan)